Nation branding in Zimbabwe: Archaeological heritage, national cohesion, and corporate identities. (October 2021) - Thondhlana, Thomas Panganayi; Chitima, Simbarashe Shadreck; Chirikure, Shadreck
This article critically assesses how heritage has been appropriated in various contexts to create national, partisan, and corporate identities in Zimbabwe. Using iconography, we attempt to establish how various players have created visual identities based on iconic archaeological artefacts and places. We discern that archaeological evidence has played a vital role in the invention and re-invention of national identity and patriotic iconography. Archaeological evidence has influenced the branding of corporate bodies, including universities, which are the major focus of this paper. Visual manifestations of the ancient Zimbabwe Culture ( madzimbahwe ), especially Great Zimbabwe, dominate the branding process. The Zimbabwe bird, Conical Tower, and motifs associated with the drystone built heritage form the key visual elements in the country's branding enterprise. We advance the argument that the period associated with madzimbahwe has been projected as the only 'Golden Age' of ancient Zimbabwe. Consequently, other heritages, diverse histories, and past cultural achievements have been marginalised.